Mali : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Joint Staff Advisory Note (JSAN) reviews the second Poverty Reduction Strategy Paper (known as the Growth and Poverty Reduction Strategy Framework, GPRSF) for the period 2007-2011 prepared by the government of Mali. To attain its twin objectives of rapid private sector-led growth and stronger public sector performance, the GPRSF outlines three strategic orientations. Private sector growth needs to be enhanced for Mali to achieve higher growth rates over the next years. The GPRSF provides a reasonable framework for implementing the government's growth and poverty reduction agenda.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet